Petroglifos en la quebrada Morín y La Galgada: de los textos gráficos al mito etiológico * - Bueno Mendoza, Alberto (2006)
Art rock constitutes for archaeology, true texts graphical autoinformativos, because it emerges in the sociocultural context of the territory in that the men are based and have installed their life, from which acquire empirical forms of knowledge, whose sensations caught and graficadas in the studied petrogliphys, they are for us true spontaneous visions of that reality.